Analysis of Clean and Healthy Living Behavior (PHBS) Post-Pandemic in Preventing Infectious Diseases in the Community - Muti Atun Nafi’ah (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
Post-pandemic Clean and Healthy Living Behavior (PHBS) has become a crucial pillar in preventing communicable diseases within families, schools, and communities. The COVID-19 pandemic accelerated the adoption of hygiene practices such as handwashing, mask-wearing, respiratory etiquette, and social distancing, which were previously uncommon in many regions. This study employed a qualitative research design, utilizing in-depth interviews, focus group discussions, and direct observations to explore post-pandemic PHBS practices, preventive measures, and associated challenges. Participants included individuals, educators, students, and community health cadres, providing comprehensive insights across multiple social levels. The findings indicate that PHBS practices have strengthened significantly, with high adherence to handwashing and mask use at the individual level, structured hygiene routines in educational institutions, and widespread community campaigns enhancing social learning. However, challenges such as limited facilities, cultural barriers, lapses in motivation, and inconsistent reinforcement were identified. Despite these obstacles, participants acknowledged the relevance of PHBS beyond COVID-19, particularly in preventing tuberculosis, diarrhea, and other infectious diseases. The study concludes that sustaining PHBS post-pandemic requires an integrated approach combining individual behavior, institutional policies, and community engagement, supported by accessible facilities and continuous education. Multi-level interventions are essential for long-term adherence and effective prevention of communicable diseases